Aplikasi Virtual Tour Manasik Haji Pada Asrama Haji Menggunakan Metode MDLC Berbasis Android - Mhd Amru Hidayat; Ali Ikhwan; Muhamad Alda (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
The increasing number of pilgrims from year to year, the more guidelines are needed that can help the community in facilitating the implementation of the pilgrimage. Meanwhile, the inefficient delivery of information regarding the practice or procedures for Hajj rituals at the Medan Hajj Dormitory is done manually by coming directly to the location. There are several things that need to be considered, namely how to design and create a virtual Hajj pilgrimage tour application by implementing the Android-based virtual joystick feature. The necessary data were collected using qualitative data collection methods, namely by conducting observations, interviews and literature studies. While the system development uses the Multimedia Development Life Cycle (MDLC) method. The resulting application is a Hajj ritual simulation application with a virtual joystick feature to move the ritual object so that it can become an interesting educational medium which has been tested using the black box testing method with a system success index of 100%.